Peak : the new science of athletic performance that is revolutionizing sports - Bubbs, Marc (White River Junction, Vermont : Chelsea Green Publishing, 2019)
"There is a new revolution happening in sports as more and more athletes are basing their success on this game-changing combination: health, nutrition, training, recovery, and mindset. Unfortunately, the evidence-based techniques that the expert PhDs, academic institutions, and professional performance staffs follow can be in stark contrast to what many athletes actually practice. When combined with the noise of social media, old-school traditions, and bro-science, it can be difficult to separate fact from fiction. Peak is a groundbreaking book exploring the fundamentals of high performance (not the fads), the importance of consistency (not extreme effort), and the value of patience (not rapid transformation). Dr. Marc Bubbs makes deep science easy to understand, and with information from leading experts who are influencing the top performers in sports on how to achieve world-class success, he lays out the record-breaking feats of athleticism and strategies that are rooted in this personalized approach.Dr. Bubbs expertly brings together the worlds of health, nutrition, and exercise and synthesizes the salient science into actionable guidance. Regardless if you
Includes bibliographical references (pages 321-356) and index.
Keywords: Physical fitness -- Health aspects; Exercise -- Physiological aspects; Nutrition; HEALTH & FITNESS / Exercise; SPORTS & RECREATION / Training; MEDICAL / Physical Medicine & Rehabilitation; HEALTH & FITNESS / Nutrition; MEDICAL / Sports Medicine; SPORTS & RECREATION / Triathlon; MEDICAL / Holistic Medicine